1999
DOI: 10.1111/j.1469-7793.1999.769ab.x
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic transmission at nicotinic acetylcholine receptors in rat hippocampal organotypic cultures and slices

Abstract: Despite its predominant role in the peripheral nervous system and particularly at the motor endplate where it was first discovered, fast nicotinic cholinergic transmission has been found up to now only exceptionally in the central nervous system. One classic example is the synaptic activation of the Renshaw cell in the spinal cord, which receives a cholinergic nicotinic input from motoneurones (Eccles et al. 1954). Similarly, synaptic nicotinic potentials have been reported in brainstem vagal motoneurones (Zha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 29 publications
3
102
1
Order By: Relevance
“…The postsynaptic response is mediated by ␣4␤2-like nAChRs (Dourado and Sargent, 2002). Other examples have now emerged, documenting nicotinic postsynaptic responses involving both ␣7-and non-␣7 nAChRs in the CNS (Zhang et al, 1993;Roerig et al, 1997;Alkondon et al, 1998;Frazier et al, 1998, Hefft et al, 1999Jones et al, 1999). Ultrastructural studies have confirmed that at least ␣4␤2-nAChRs can be found in PSDs in the rat substantia nigra (Arroyo-Jimenez et al, 1999).…”
Section: Postsynaptic/perisynaptic Sitesmentioning
confidence: 98%
“…The postsynaptic response is mediated by ␣4␤2-like nAChRs (Dourado and Sargent, 2002). Other examples have now emerged, documenting nicotinic postsynaptic responses involving both ␣7-and non-␣7 nAChRs in the CNS (Zhang et al, 1993;Roerig et al, 1997;Alkondon et al, 1998;Frazier et al, 1998, Hefft et al, 1999Jones et al, 1999). Ultrastructural studies have confirmed that at least ␣4␤2-nAChRs can be found in PSDs in the rat substantia nigra (Arroyo-Jimenez et al, 1999).…”
Section: Postsynaptic/perisynaptic Sitesmentioning
confidence: 98%
“…The synapses formed by cholinergic neurons onto spiny neurons have not been shown to generate synaptic currents by way of ionotropic nicotinic receptors, but act primarily in a modulatory fashion (Uchimura and North, 1990;Howe and Surmeier, 1995;Galarraga et al, 1999;Gabel and Nisenbaum, 1999;Calabresi et al, 2000). It is possible, however, that a small excitatory synaptic response mediated by nAChRs has gone undetected and could contribute to the modulatory cholinergic action, as is the case in the hippocampus (Alkondon et al, 1998;Frazier et al, 1998;Hefft et al, 1999). Spiny neurons do express muscarinic m1 and sometimes m4 receptors (Hersch et al, 1994;Alcantara et al, 2001;Yan et al, 2001) that modulate voltage-gated channels.…”
Section: Consequences Of the Activity Of Cholinergic Interneuronsmentioning
confidence: 99%
“…Prolonged exposure to low concentrations of nicotine decreases the ACh sensitivity of the GABAergic input to interneurons. Hippocampal interneurons are one of the few cell types that have been shown to receive cholinergic synaptic input mediated by nAChRs (Frazier et al, 1998a;Hefft et al, 1999). It will be interesting to learn more about nicotine's effects on the contribution of these neurons to the circuitry of the hippocampus.…”
Section: Nicotinic Modulation Of Gabaergic Transmission In the Vtamentioning
confidence: 99%